QoS in Packet Networks - Park, Kun I. (The Springer International Series in Engineering and Computer Science,, 2005)
QoS is an important subject which occupies a central place in overall packet network technologies. A complex subject, its analysis involves such mathematical disciplines as probability, random variables, stochastic processes and queuing. These mathematical subjects are abstract, not easy to grasp for uninitiated persons. QoS in Packet Networks is written with two objectives. The first explains the fundamental mathematical concepts used in QoS analysis as plainly as possible, in layman's terms to afford the reader a better appreciation of the subject of QoS treated in this book. The second explains in plain language, the various parts of QoS in packet networks, to provide the reader with a complete view of this complex and dynamic area of communications networking technology. Discussion of the functional requirements of the packet networks to provide QoS is included. QoS in Packet Networks is designed for a professional audience composed of researchers and practitioners in industry. This volume is also suitable for graduate-level students in computer science and electrical engineering.